The Moderating Effect of Educational Achievement on the Relationship Between Personality and Leadership Indifference - Wan Najwa Arifah, W. Ahmad (2011)
This exploratory study looked into the relationship between personality and leadership indifference among students of tertiary education of Universiti Utara Malaysia (UUM), Politeknik Sultan Abdul Halim Muadzam Shah (POLIMAS), and Institut Kemahiran Bina Negara (IKBN) at Kedah. Other than that, the aspects explored in this study included the differences between the selected demographic variables of gender and educational background to be a leader. The research was a quantitative survey carried out of 174 respondents. The instruments used were the Personality Inventory (Kauzes and Posner, 1997) and the rest of the questions are about leadership indifference and educational achievement. There was a significant relationship between personality and leadership indifference. But, there were no significant differences between gender and educational background in both leadership and personality.